Overview of test methods to determine strength and plastic properties of the wire - M. A. Kukharenko (Litʹë i Metallurgiâ, 2018)
The article presents various methods for determining the strength and plastic properties of the wire to assess the quality characteristics of the products produced in the steel shops of JSC «BMW – the Management Company of the Holding «BMC».The methods of determining the propensity of a thin wire to laminations by reversing the twisting («Swedish» twist) and unilateral twisting, fixing the length change of the sample with a prefix with the dial indicator are considered. The article describes the procedure and results of research to determine the effect of the ratio of the conditional yield strength to the time resistance of the rupture on the plastic properties of the wire, the type of tensile diagram of the wire fragility.